Analysis of the comparison of the levels of concentration and meditation in the realization of academic activities and activities related to videogames, based on brain computer interface - Auccahuasi, W. (2019)
In the new times we are living, the use of technology is causing many of the customs are changing, one of them is the development of children, in previous years children used to play with their friends in the parks, technology It has caused many of them to perform recreation activities based on the use of video games, these games have caused children to develop certain skills and also change their behavior when they perform certain activities, in this work a comparison between the levels of concentration and meditation levels when children carry out activities related to the realization of academic activities related to the accomplishment of the school tasks that they must perform, with the levels of concentration and meditation when the child is doing activities related to video games, methodology that was used to evaluate the levels The concentration and meditation is based on the use of the Neurosky MindWave EEG device, which gives us the level of concentration and meditation that the person is on a scale of 0% to 100%, the results obtained show that In the case of videogames, children develop high levels of concentration in almost the entire development of the game from the beginning to the end of the game, compared to the levels that they develop when they do their homework, where children hardly concentrate having average records on average in the level of concentration and meditation.